Electrochemical and rheological properties of phthaloyl starch and hydroxyethyl cellulose blend- based gel polymer electrolyte for application in quasi-solid Dye-sensitized solar cell / Vidhya Selvanathan - Vidhya , Selvanathan (2018)
In this work, a simple phthaloylation process involving reaction of starch with phthalic anhydride is proposed to transform starch into organosoluble material. FTIR and NMR spectroscopy results verifies the formation of phthaloyl starch (PhSt). The resulting starch derivative, was then blend with hydroxyethyl cellulose (HEC) to fabricate polymer gel electrolytes. Rheological analyses such as amplitude sweep studies and tack tests indicate that gels with good rigidity, strength and adhesiveness were attained upon blending 20 to 60 wt.% HEC. Gels within this optimum range of composition were then fabricated into quasi-solid dye-sensitized solar cell (QSDSSC) with the addition of 5 wt.% of tetrapropylammonium iodide and iodine. EIS of the QSDSSC reveal that the adhesive property of the gels plays a crucial role in affecting charge transfer processes at the electrode/electrolyte interfaces. The highest efficiency of 3.02% was recorded with the gels consisting 70 wt.% of PhSt and 30 wt.% of HEC. This polymer blend composition was then used to study the effect of salt composition on the electrolyte properties in which two series of polymer gels containing different amounts of tetrapropylammonium iodide (TPAI) and lithium iodide (LiI) respectively were prepared. Storage modulus values from rheological studies showed that the size of cations in the electrolytes affects the mechanical property of the gels. Best performing solar cells with the efficiency of 3.94 % was achieved by addition of 12.5 wt.% of TPAI. As an initiative to further boost the efficiency values, 1-butyl-3-methylimidazolium iodide (BMII) was included into the PhSt-HEC-TPAI system. The ionic liquid greatly enhanced the short circuit current of the cells, leading to an optimum efficiency of 5.20 % upon addition of 8 wt.% of BMII.